Depression, Stigma, and Quality of Life among Elderly with HIV/AIDS in Bali - Ni Made Diah Pusparini Pendet; Sri Yona; Yulia (Babali Health, 2020)
Introduction: Quality of life is a significant aspect of care among the elderly with HIV/AIDS. The aging process affects their physical, physiological, and social function. Depression due to perceived stigma from the community also influences their quality of life. This study aimed to analyze the correlation between depression and stigma on the quality of life among the elderly with HIV/AIDS. Methods: This was a cross-sectional study employed 67 participants were selected by purposive sampling. Results: Results showed that the majority of participants experienced depression (64.2%) and stigma (76.1%), but they are still classified on good quality of life category (64.2%). Analysis showed that there was a significant correlation between quality of life and depression, & and stigma (p=0.021, p=0.031, α=0.05). Result from logistic regression statistical analysis also revealed that stigma and depression affected the poor quality of life after controlled by gender, occupational status, education, clinical stadium, comorbidities, duration of disease, living and marital status, with the p-value 0.029 and 0.014 (CI=95%), respectively. Conclusion: Promotive and preventive efforts required to be implemented in reducing stigma on the elderly with HIV/AIDS. Screening program also would help prevent depression among this vulnerable group.